2020
DOI: 10.1371/journal.pone.0226978
|View full text |Cite
|
Sign up to set email alerts
|

Playing tactics, contextual variables and offensive effectiveness in English Premier League soccer matches. A multilevel analysis

Abstract: The aim of this study was to investigate the combined effects of tactical and contextual indicators on achieving offensive penetration and scoring opportunities in English Premier League (EPL) soccer matches. A total of 1971 team possessions from 20 random matches were evaluated by means of multidimensional observation. The EPL matches had a great proportion of fast attacks (36.0%) followed by combinative (29.6%), direct attacks (24.1%) and counterattacks (9.5%). Multilevel logistic regression models revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…Although there is no commonly used definition of GSO, it is usually applied to address conditions with high expected probability to result in a goal, which are normally situations where shots is released from the slot area (deemed zone 1 and 2 in this study). In comparable sports such as soccer, GSO is a commonly applied term and has been a focus in several studies (González-Rodenas et al, 2020;Wright et al, 2011). Comparable to our study, González-Rodenas et al (2020) defined GSO in a soccer game as all shots and chances to shoot inside a specific area close to the goal, while (Wright et al, 2011) in contrast deemed a GSO as a general term for all shots.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Although there is no commonly used definition of GSO, it is usually applied to address conditions with high expected probability to result in a goal, which are normally situations where shots is released from the slot area (deemed zone 1 and 2 in this study). In comparable sports such as soccer, GSO is a commonly applied term and has been a focus in several studies (González-Rodenas et al, 2020;Wright et al, 2011). Comparable to our study, González-Rodenas et al (2020) defined GSO in a soccer game as all shots and chances to shoot inside a specific area close to the goal, while (Wright et al, 2011) in contrast deemed a GSO as a general term for all shots.…”
Section: Discussionsupporting
confidence: 45%
“…In comparable sports such as soccer, GSO is a commonly applied term and has been a focus in several studies (González-Rodenas et al, 2020;Wright et al, 2011). Comparable to our study, González-Rodenas et al (2020) defined GSO in a soccer game as all shots and chances to shoot inside a specific area close to the goal, while (Wright et al, 2011) in contrast deemed a GSO as a general term for all shots. In our study, 13.2% of the GSO were converted into goal, which is a similar goal scoring ratio (15.2%) that was found in soccer when analysing all shots in a game (Gonzalez-Rodenas et al, 2020).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In summary, this means that the relations between these variables are non-existent or non-linear. Differences in the effectiveness of attacking styles have been reported in the literature 51 , which could lead to different behavioral patterns (and, hence, differences in physical parameters). However, in the current study, we analyzed the association between the frequency of different attacking styles and the physical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Further potentially influencing the balance of a defense is the amount of time that a possession takes to move the ball from defensive zone to the offensive or scoring area. Gonzalez-Rodenas et al, found that, in the English premier league, possessions longer than 10 seconds resulted in a higher likelihood of offensive penetration but not in creating greater scoring chances [13]. This finding was in contradiction of findings in other leagues [7,8,14] where longer possessions were more effective.…”
Section: Introductionmentioning
confidence: 94%